2023
DOI: 10.3389/fneur.2023.1210103
|View full text |Cite
|
Sign up to set email alerts
|

Multi-session transcutaneous auricular vagus nerve stimulation for Parkinson's disease: evaluating feasibility, safety, and preliminary efficacy

Daniel H. Lench,
Travis H. Turner,
Colin McLeod
et al.

Abstract: BackgroundIn pre-clinical animal models of Parkinson's disease (PD), vagus nerve stimulation (VNS) can rescue motor deficits and protect susceptible neuronal populations. Transcutaneous auricular vagus nerve stimulation (taVNS) has emerged as a non-invasive alternative to traditional invasive cervical VNS. This is the first report summarizing the safety, feasibility, and preliminary efficacy of repeated sessions of taVNS in participants with PD.ObjectivesTo evaluate the feasibility, safety, and possible effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, even if the therapeutic usefulness of taVNS is still questionable, our results show early proofs of neural engagement. 27,28 With the current methodology it is not possible to draw any further conclusion on the association between gait speed changes and β power. Indeed, the latter is an acknowledged biomarker of bradykinesia and rigidity and of their modulation through therapies, 29 and its relationship with gait is controversial.…”
Section: Discussionmentioning
confidence: 94%
“…However, even if the therapeutic usefulness of taVNS is still questionable, our results show early proofs of neural engagement. 27,28 With the current methodology it is not possible to draw any further conclusion on the association between gait speed changes and β power. Indeed, the latter is an acknowledged biomarker of bradykinesia and rigidity and of their modulation through therapies, 29 and its relationship with gait is controversial.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent research has focused on this region primarily for transcutaneous vagal nerve stimulation (tVNS), thought to affect activity in the nucleus tractus solitarus and locus coeruleus, which relay afferent sensory information via connections to the thalamus, orbitofrontal cortex, and medulla [ 131 , 132 ]. Multiple recent studies found tVNS improved various gait parameters in people with PD, including those with FoG, however, had mixed success in improving UPDRS III scores [ [133] , [134] , [135] , [136] , [137] ]. While these results suggest its promise in treating gait impairments in PD, tVNS’ effects on PIGD symptoms remain relatively unknown.…”
Section: Additional Neuromodulatory Interventions On Postural Instabi...mentioning
confidence: 99%